THE EFFECTIVENESS OF THE PROSPEROUS HOUSING PROGRAM IN HULU SUNGAI SELATAN REGENCY AT SOUTH KALIMANTAN PROVINCE - Sukmana, Mochammad Syachrur; Praja, Selvia Junita (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
Abstract: This research was initiated due to the level of social welfare of the community in Hulu Sungai Selatan Regency is still relatively low, which is characterized by the large number of uninhabitable residences. The aim of this research is to assess the effectiveness of the Prosperous Housing Program (PRS) policy stipulated in Hulu Sungai Selatan Regency Regent Regulation No. 25 of 2015 concerning Integrated Regional Poverty Management in Hulu Sungai Selatan Regency in increasing the number of livable housing for the community in Hulu Sungai Selatan Regency as well as knowing the obstacle factors, and the efforts to solve them. This research used a descriptive qualitative research method with an inductive approach. Data collection technique used in this research were interviews, documents and data, as well as observation. Interviews were conducted with related parties. Researchers also analysed the data using Riant Nugroho's theory regarding Policy Effectiveness. The research results show that the implementation of the Prosperous Housing Program (PRS) in improving the quality of community housings can be said to be successful and effective because it meets the achievement targets every year. However, there are still several obstacles to implementing this program. These obstacles are influenced by several factors, including lack of coordination between program implementing parties, short program implementation time, limited workforce and land ownership problems. Meanwhile, the efforts to solve the obstacles include forming a coordination team, careful time planning, increasing the quality and quantity of labour and providing information regarding land ownership. Keywords: Policy Effectiveness, Habitable Housings, Community.